2020
DOI: 10.1021/acs.iecr.9b05377
|View full text |Cite
|
Sign up to set email alerts
|

Density and Phase Behavior of the CO2 + Methylbenzene System in Wide Ranges of Temperatures and Pressures

Abstract: Knowledge of the thermophysical properties of CO2-hydrocarbon mixtures over extended ranges of temperature and pressure is crucial in the design and operation of many carbon capture and utilization processes. In this paper, we report saturated-phase densities, compressed-liquid densities and phase behaviour of CO2 + methylbenzene at temperatures between (283 and 473) K and at pressures up to 65 MPa over the full composition range. The saturated-phase densities were correlated by a recently-developed empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 61 publications
(216 reference statements)
2
8
0
Order By: Relevance
“…At T < 373 K, the liquid phase densities at first increased with pressure until a maximum was reached, after which the values declined up to the critical point. This behavior, which was particularly noticeable at temperatures of 298−323 K, has been observed for other (CO 2 + hydrocarbon) binary systems 17,18 and is attributed to the influence of CO 2 dissolving a ρ c and p c represent the critical density and pressure, respectively. The values of the average absolute deviation Δ AAD and average absolute relative deviation Δ AARD between the experimental densities and those calculated by eq 2.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…At T < 373 K, the liquid phase densities at first increased with pressure until a maximum was reached, after which the values declined up to the critical point. This behavior, which was particularly noticeable at temperatures of 298−323 K, has been observed for other (CO 2 + hydrocarbon) binary systems 17,18 and is attributed to the influence of CO 2 dissolving a ρ c and p c represent the critical density and pressure, respectively. The values of the average absolute deviation Δ AAD and average absolute relative deviation Δ AARD between the experimental densities and those calculated by eq 2.…”
Section: Resultssupporting
confidence: 57%
“…To assist in developing thermodynamic models, we have investigated the thermophysical properties of several (CO 2 + hydrocarbon) systems over wide pressure and temperature ranges. Specifically, our group has reported densities and vapor–liquid equilibrium (VLE) data for the systems (CO 2 + n -heptane) and (CO 2 + methylbenzene), both mixtures involving a hydrocarbon containing seven carbon atoms. In this paper, we present the saturated-phase densities for another system of that type: (CO 2 + methylcyclohexane). Several authors have reported VLE data for this system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binary parameters can be obtained from empirical models that can satisfactorily describe the thermodynamics of this type of amine solutions for wide ranges of temperatures and pressures. 5 The electrochemically mediated amine regeneration (EMAR) is an alternative method to the conventional thermal regeneration of amines aimed at reducing the energy demand of the CO 2 capture process. The EMAR process does not require steam integration, because only electrical energy is used for the regeneration of the solvent.…”
Section: ■ Co 2 Capturementioning
confidence: 99%
“…A deep knowledge of CO 2 –hydrocarbon mixtures is essential for the design and operation of absorption systems. Binary parameters can be obtained from empirical models that can satisfactorily describe the thermodynamics of this type of amine solutions for wide ranges of temperatures and pressures …”
Section: Co2 Capturementioning
confidence: 99%